Case report: Flow changes in routes of collateral circulation in patients with LVO and low NIHSS: a point favor to treat - Santos Neto, Elizeu Pereira dos; de Sousa, Ícaro Araújo; Veras, Arthur de Oliveira; Barros-Araújo, Marx Lima de; Ricarte, Irapuá Ferreira; Pontes-Neto, Octávio Marques (Frontiers in Neurology, 2023)
The effectiveness of endovascular thrombectomy in patients presenting low National Institutes of Health Stroke Scale (NIHSS) scores remains controversial, and the acquisition of additional evidence is required to refine the selection of candidates who may benefit the most from this therapeutic modality. In this study, we present the case of a 62-year-old individual, with left internal carotid occlusion stroke and low NIHSS, who had compensatory collateral flow from Willis polygon via the anterior communicating artery. The patient subsequently exhibited neurological deterioration and collateral flow failure from Willis polygon, indicating the need for urgent intervention. The study of collaterals in patients with large vessel occlusion stroke has garnered considerable attention, with research suggesting that individuals with low NIHSS scores and poor collateral profiles may be at a heightened risk of early neurological deterioration. We postulate that such patients may derive significant benefits from endovascular thrombectomy, and may posit that an intensive transcranial Doppler monitoring protocol could facilitate the identification of suitable candidates for such intervention.